A spiral shaped regenerative microfluidic fuel cell with Ni‐C based porous electrodes. (29th August 2019) - Arun, Ravi Kumar; Anjali,; Sardar, Moumita; Singh, Preeti; Jha, Bishnu Mohan; Chanda, Nripen
Summary: Microchannel geometry, electrode surface area, and better fuel utilization are important aspects of the performance of a microfluidic fuel cell (MFC). In this communication, a membraneless spiral‐shaped MFC fabricated with Ni as anode and C as a cathode supported over a porous filter paper substrate is presented. Vanadium oxychloride and dilute sulfuric acid solutions are used as fuel and electrolyte, respectively, in this fuel cell system. The device generates a maximum open‐circuit voltage of ~1.2 V, while the maximum energy density and current density generated from the fuel cell are ~10 mW cm −2 and ~51 mA cm −2, respectively. The cumulative energy density generated from the device after five cycles are measured as ~200 mW after regeneration of the fuel by applying external voltage. The spiral design of the fuel cell enables improved fuel utilization, rapid diffusive transport of ions, and in‐situ regeneration of the fuel. The present self‐standing spiral‐shaped MFC will eliminate the challenges associated with two inlet membrane‐less fuel cells and has the potential to scale up for commercial application in portable energy generation. Abstract : A spiral‐shaped regenerative microfluidic fuel cell using porous Paper@Ni‐ and Paper@C‐based electrode uses a fuel‐electrolyte mixture of 0.025 M VOCl3/dil. H2 SO4 to generate energy. The spiral geometry of the microchannel facilitates the in situ regeneration of the fuel enhance the shelf life of the device by eliminating the need to frequently re‐fuelling the device with fresh fuel.